Changes in bile acid profiles and short-term weight loss in response to a low-calorie diet: a pilot study - Jiang, Ming-Xia; Ling, Chen-Jie; Qian, Si-Cheng; Zhai, Jing-Nan; Huang, Jin-Yuan; Su, Ke-Ke; Wu, Xiang-Wei; Han, Qing-Zhen; Wang, Lin (Frontiers in Nutrition, 2025)
BackgroundDietary intervention-induced modulation of bile acids may enhance metabolic homeostasis and facilitate weight reduction. We aimed to elucidate the role of bile acids and their association with the gut microbiota during weight reduction induced by a low-calorie diet (LCD).MethodsTwelve participants were enrolled, and body composition, serum bile acid profiles, and gut microbiota were analyzed at baseline and after a 4-week LCD intervention.ResultsThe LCD significantly reduced body weight (3.39 ± 1.99 kg, p < 0.001) and body fat (2.47 ± 2.00 kg, p = 0.001), accompanied by decreases in skeletal muscle mass (0.59 ± 0.55 kg, p = 0.003), serum iron, magnesium, uric acid, and triglyceride (TG) levels. Notably, serum lithocholic acid levels increased significantly and were negatively correlated with TG levels and positively correlated with Faecalibacterium abundance. The LCD also decreased the relative abundances of Streptococcaceae and Streptococcus, while increasing Porphyromonadaceae, Christensenellaceae, Parabacteroides, and Oscillospira.ConclusionThese findings suggest that increased LCA is associated with metabolic improvements during LCD intervention.